Bumiputra small and medium enterprises in Kuching: a study on their awareness towards the guarantee schemes provided by Credit Guarantee Corporation Malaysia Berhad / Sulaiman Abdullah - Abdullah, Sulaiman (2007)
Banks are important sources of external credit but they are reluctant to lend to small and medium enterprises (SMEs) due to the high credit risk involved. Therefore, Credit Guarantee Corporation Malaysia Berhad was set up to assist SMEs to secure loans from financial institutions in Malaysia. Being the sole issuer of credit guarantees to SMEs, the performance of CGC directly reflects the availability of credit guarantees to SMEs. Hence to ascertain the accessibility of credit guarantees, this study evaluates the efficiency of credit guarantee schemes provided by CGC. From a non-parametric analysis, CGC is found to be operating at a relatively low level of overall technical efficiency. Therefore CGC should consider reallocating its existing inputs as well as increase the amount of credit guarantees granted to SMEs in order to achieve a reasonable level of efficiency.